Obtenção e caracterização de microencapsulados enriquecidos com polifenóis extraidos da polpa do maracujá (Passiflora edulis) - Barros, Elenita Marinho Albuquerque (2019)
Nutraceuticals are food supplements that contain the concentrated form of one or more bioactive compounds extracted from food, being presented separately from the food matrix and used for therapeutic purposes at doses exceeding those that could be obtained from in natura foods. The concentration of bioactive compounds extracted from medicinal plants, tropical fruits or functional foods in microencapsules represents a route for use of such products for therapeutic purposes. Thus, the objective of this work was the production of nutraceutical microencapsulates produced from polyphenols extracted from passion fruit pulp (Passiflora edulis). For the production of the microencapsulates, passion fruit pulp was used, followed by the emulsification technique with nutraceutical additives and immediate drying by the Spray-Dryer technique, to obtain the microparticles. Initially, three emulsification techniques with nutraceutical additives (preparations 1, 2 and 3) were tested, and the preparation that presented better drying stability (preparation 1), was used to carried out with the preparation of formulations 1, 2 and 3. The microencapsules obtained from the formulations, as well as the passion fruit pulp, were submitted to physicochemical characterization, through thermal analysis, X-ray diffraction, infrared analysis, particle size, quantification and identification of phenols and flavonoids, chromatographic profile , scanning electron microscopy (SEM) and in vitro test, in addition to the evaluation of the antioxidant potential through the DPPH, FRAP and ABTS analyzes. For the in vitro test, the action of passion fruit pulp on the growth of Staphylococcus aureus, S. epidermidis, Escherichia coli, Pseudomonas aeruginosa and Candida albicans was evaluated. Thermal analysis results showed that formulation 2, showed better heat stability, with lower pasta. In relation to RX diffraction all the formulations presented similar behavior. In the infrared analysis, formulation 2 presented better protection by the encapsulating agents and in SEM, the encapsulating effect in the formulations is clearly evident. In the chromatographic profile of the pulp, it observed the presence of chlorogenic acid and apigenin, both extracted with HCl and EtOAC (ethyl acetate). As for the antioxidant capacity of passion fruit pulp, the best antioxidant effect was demonstrated by the DPPH method. As for the in vitro tests, evaluations against the growth of S. aureus, S. epidermidis, E. coli, P. aeruginosa and C. albicans, indicated that the microencapsulated with passion fruit pulp present an inhibitory effect on the growth of these pathogenic microorganisms, presenting therapeutic potential in combat infections. It can be seen that the microencapsules prepared with gelatin, starch, aerosil, ethanol and water (formulation 1 and 2) presented the best stability to the drying process, presenting good thermal stability and RX and infrared diffraction profile similar to of passion fruit pulp.